Perceived support for recovery and level of functioning among people with severe mental illness in Central and Eastern Europe: an observational study - Roth, Catharina; Wensing, Michel; Koetsenruijter, Jan; Istvanovic, Ana; Novotni, Antoni; Tomcuk, Aleksandr; Dedovic, Jovo; Djurisic, Tatijana; Milutinovic, Milos; Kuzman, Martina Rojnic; Nica, Raluca; Bjedov, Sarah; et al. (Frontiers in psychiatry, 2021)
Background: Many people with severe mental illness experience limitations in personal and social functioning. Care delivered in a person's community that addresses needs and preferences and focuses on clinical and personal recovery can contribute to addressing the adverse impacts of severe mental illness. In Central and Eastern Europe, mental health care systems are transitioning from institutional-based care toward community-based care. The aim of this study is to document the level of functioning and perceived support for recovery in a large population of service users with severe mental illness in Central and Eastern Europe, and to explore associations between perceived support for recovery and the degree of functional limitations.Methods: The implementation of community mental health teams was conducted in five mental health centers in five countries in Central and Eastern Europe. The present study is based on trial data at baseline among service users across the five centers. Baseline data included sociodemographic, the World Health Organization Disability Assessment Schedule (WHODAS 2.0) for functional limitations, and the Recovery Support (INSPIRE) tool for perceived staff support toward recovery. We hypothesized that service users reporting higher levels of perceived support for their recovery would indicate lower levels of functional limitation.Results: Across all centers, the greatest functional limitations were related to participation in society (43.8%), followed by daily life activities (33.3%), and in education or work (35.6%). Service users (N = 931) indicated that they were satisfied overall with the support received from their mental health care provider for their social recovery (72.5%) and that they valued their relationship with their providers (80.3%). Service users who perceived the support they received from their provider as valuable (b = −0.10, p = 0.001) and who reported to have a meaningful relationship with them (b = −0.13, p = 0.003) had a lower degree of functional limitation.Conclusion: As hypothesized, the higher the degree of perceived mental health support from providers, the lower the score in functional limitations. The introduction of the community-based care services that increase contact with service users and consider needs and which incorporate recovery-oriented principles, may improve clinical recovery and functional outcomes of service users with severe mental illness.
Gesehen am 12.10.2021